Consumption, inflation risk and dynamic hedging - Stefan Franz Schubert; Udo Broll (Contemporary Economics, 2015)
Our study examines the behavior of a risk-averse investor who faces two sources of uncertainty: a random asset price and inflation risk. Both sources of uncertainty make it difficult to stabilize consumption over time. However, investors can enter risk-sharing markets, such as futures markets, to manage these risks. We develop a dynamic risk management model. Optimal consumption and risk management strategies are derived. It is shown that dynamic hedging increases an investor's welfare in terms of the expected inter-temporal utility of consumption.
Keywords: D21; D24; 330; Dynamic hedging; asset price risk; inflation risk; real wealth; consumption